Effects of psychological capital and person-job fit on hospitality employees' work-family conflict, family-work conflict and job performance: the moderating role of marital status - Yan, Zhen; Bai, Na; Dato Mansor, Zuraina; Choo, Wei Chong (Frontiers Research Foundation, 2022)
Drawing on the conservation of resources (COR) theory and congruence theory, this study aims to investigate the influence of psychological capital (PsyCap) and person-job fit (PJ fit) on work–family conflict (WFC), family–work conflict (FWC) and job performance (JP), especially the moderating effect of marital status on hypothesized relationships between two directions of conflicts in the work-family interface and JP. Utilizing a two-stage design, this study surveyed 312 flight attendants employed by two international airline companies in Malaysia and used the structural equation modeling technique to test the hypothesized relationships. Findings showed that PsyCap could significantly alleviate two directions of WFC simultaneously and promote employees’ JP. PJ fit was also identified to be an effective mitigator of WFC and FWC; however, a significant association between PJ fit and JP has not been found in this study. The findings further suggested that both WFC and FWC could mediate the association between PsyCap and JP. In addition, the fact that marital status resulted in disparity in the formation of JP was also evidenced. Airline companies should pay more attention to the positive impact of individual psychological determinants, such as PsyCap and PJ fit, which can effectively alleviate various issues in the work–family interface, thereby improving employees’ JP.